Black Cherokee : a novel - Downing, Antonio Michael, 1975- (Simon & Schuster, 2025)
"Ophelia Blue Rivers is a descendent of Cherokee Freedmen: Blacks formerly enslaved by rich southern Cherokee. She is "Black" but doesn't understand why that makes her different. She is "Cherokee" but struggles to know what that means. Their town of Etsi--once a reservation--still lives with the wounds of its disbanding. When the town, and the river that sustains it, are put in mortal danger personal rivalries threaten their very survival. Against this backdrop Ophelia begins her spirited, at times harrowing, search for place and family. She must discover: what does it mean to belong when belonging comes at such a high price? " --Provided by Publisher.